2021
DOI: 10.1038/s42255-021-00348-0
|View full text |Cite|
|
Sign up to set email alerts
|

Gut microbiome pattern reflects healthy ageing and predicts survival in humans

Abstract: The gut microbiome has important effects on human health, yet its importance in human ageing remains unclear. In the present study, we demonstrate that, starting in mid-to-late adulthood, gut microbiomes become increasingly unique to individuals with age. We leverage three independent cohorts comprising over 9,000 individuals and find that compositional uniqueness is strongly associated with microbially produced amino acid derivatives circulating in the bloodstream. In older age (over ~80 years), healthy indiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
303
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(383 citation statements)
references
References 63 publications
23
303
0
Order By: Relevance
“…In particular, only healthy aging mice showed significantly increased Shannon diversity with age. Consistent with previous work 68 , our study also linked aging to an increase in interindividual variation in gut microbial community composition, with interindividual variation being especially high in the normal aging group. This suggested that the unhealthy aging related changes in the gut microbiota are likely stochastic, leading to community instability.…”
Section: ∆ F Isupporting
confidence: 91%
“…In particular, only healthy aging mice showed significantly increased Shannon diversity with age. Consistent with previous work 68 , our study also linked aging to an increase in interindividual variation in gut microbial community composition, with interindividual variation being especially high in the normal aging group. This suggested that the unhealthy aging related changes in the gut microbiota are likely stochastic, leading to community instability.…”
Section: ∆ F Isupporting
confidence: 91%
“…Given its developing importance to health and disease, the gut microbiota represents a new area in healthy ageing and longevity research. Wilmanski et al [89] have described the dynamics of the gut microbiota across human life course, in a detailed phenotyping of 9000 subjects spanning 18-101 years of age. This investigation has revealed that the gut microbiota tends to become more unique to respective individuals with increasing chronological age, and this 'uniqueness' was characterised by a distinct shift in plasma gut microbial metabolites, with significant changes in phenylalanine and tryptophan pathways.…”
Section: Of Microbiome and Menmentioning
confidence: 99%
“…There is enough evidence available to suggest a correlation between gut dysbiosis, longevity and the prevalence of chronic disorders (Cardenas et al, 2014;Kamo et al, 2017;Lee et al, 2019). In fact, a recent report highlights that gut microbiome composition is a predictor of human survival and increased abundance of Bacteroides or low gut microbiome uniqueness is associated with decreased lifespan and enhanced morbidity (Wilmanski et al, 2021). Based on machine learning, another recent report inferred that age-related changes in the gut microflora can be used to precisely predict the age of an individual (Galkin et al, 2020).…”
Section: Gut Microbiota In Aging and Associated Diseasesmentioning
confidence: 99%